DECENTRALIZATION AND THE LOCAL DEVELOPMENTAL STATE: PEASANT MOBILIZATION IN OROMIYA, ETHIOPIA. (6th April 2016) - Emmenegger, Rony
ABSTRACT: This article explores the politics of decentralization and state–peasant encounters in rural Oromiya, Ethiopia. Breaking with a centralized past, the incumbent government of the Ethiopian People's Revolutionary Democratic Front (EPRDF) committed itself to a decentralization policy in the early 1990s and has since then created a number of new sites for state–citizen interactions. In the context of electoral authoritarianism, however, decentralization has been interpreted as a means for the expansion of the party-state at the grass-roots level. Against this backdrop, this article attempts a more nuanced understanding of the complex entanglements between the closure of political space and faith in progress in local arenas. Hence, it follows sub- kebele institutions at the community level in a rural district and analyses their significance for state-led development and peasant mobilization between the 2005 and 2010 elections. Based on ethnographic field research, the empirical case presented discloses that decentralization and state-led development serve the expansion of state power into rural areas, but that state authority is simultaneously constituted and undermined in the course of this process. On that basis, this article aims to contribute to an inherently political understanding of decentralization, development and their entanglement in local and national politics in rural African societies. RÉSUMÉ: Cet article explore la politique de décentralisation et les rapports État-paysans dans la région éthiopienne rurale d'Oromia. En rupture avec un passé centralisé, le gouvernement de l'EPRDF (Ethiopian People's Revolutionary Democratic Front) s'est engagé dans une politique de décentralisation au début des années 1990 et a créé depuis lors de nouveaux sites d'interaction État-citoyen. Dans le contexte d'autoritarisme électoral, cependant, la décentralisation a été interprétée comme un moyen d'expansion de l'État-parti au niveau des citoyens ordinaires. Dans ce contexte, l'article tente une interprétation plus nuancée des entremêlements complexes entre la fermeture de l'espace politique et la foi dans le progrès dans les arènes locales. À cette fin, il suit des institutions sous- kebele au niveau communautaire dans un district rural et analyse leur poids dans le développement dirigé par l'État et la mobilisation paysanne entre les élections de 2005 et de 2010. À partir de travaux de recherche ethnographiques sur le terrain, le cas empirique présenté révèle que la décentralisation et le développement dirigé par l'État servent l'expansion du pouvoir de l'État dans les zones rurales, mais que l'autorité de l'État est simultanément constituée et sapée au cours de ce processus. Fort de ce constat, l'article vise à contribuer à une interprétation intrinsèquement politique de la décentralisation, du développement et de leur entremêlement dans la politique locale et nationale des sociétés africaines rurales.